LIGHTING ON UNREGULATED PEDESTRIAN CROSSING - S. N. Pavlov; Yu. V. Pavlova (Вестник СибАДИ)
Introduction. The actual problem in Russia is the accident rate at pedestrian crossings. The authors conduct the research about the lighting conditions on unregulated pedestrian crossings to improve safety and to identify compliance with current regulations. Moreover, International and Russian researchers point out a large role in ensuring visibility of pedestrians. Increasing of the roadway lightness improves the visibility of pedestrians at night, especially at pedestrian crossings. In addition, world practice shows that after improving the road lighting the number of accidents with pedestrians decreases.Materials and methods. The authors selected unregulated pedestrian crossings, which were the sources of accidents in dark period. The light level was measured using a Victor 1010A light meter. The authors carried out the dimensions at night in clear weather without precipitation, when artificial lighting was turned on.Results. The research revealed that the lighting at pedestrian crossings and especially at the crossings’ approaches did not correspond to standard values even with the artificial lighting. Therefore, the lighting on approaches was important for early pedestrians’ detection by drivers.Discussion and conclusions. As a result, the authors present the recommendations for the insufficient visibility’s elimination at the pedestrian crossings. The authors also justify the need to control the lighting level at all unregulated pedestrian crossings and approaches to them.